1992
DOI: 10.1002/crq.3900090404
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent development and family dynamics: Delineating a knowledge base for family mediation

Abstract: To facilitate the mediation process and resolve family conflicts involving an adolescent optimally, practicing mediators must have a conceptual understanding and theoretical framework of adolescence. The purpose of this article is to review what we know about normative adolescent development, highlighting how adolescents generally cope with stressors and conflict and identifying effects of their development on family dynamics. Implications for practice are discussed by identifying key underlying developmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1992
1992
1998
1998

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The findings from the Van Slyck, Stern, and Newland (1992) study concerning the preintervention FES profiles for both adolescents and parents elucidates this issue. These profiles indicated that the adolescents involved were indeed distressed.…”
Section: Theoretical Integrationmentioning
confidence: 96%
See 4 more Smart Citations
“…The findings from the Van Slyck, Stern, and Newland (1992) study concerning the preintervention FES profiles for both adolescents and parents elucidates this issue. These profiles indicated that the adolescents involved were indeed distressed.…”
Section: Theoretical Integrationmentioning
confidence: 96%
“…Van Slyck, Stern, and Newland (1992) conducted a study on parentchild mediation that examined the relationship among aspects of family functioning and characteristics of the presenting problem assessed prior to intervention and mediation outcome and subsequent family functioning. The study attempted to advance our knowledge of parent-child mediation through the use of standardized and empirically derived measures.…”
Section: Research On Parent-child Mediationmentioning
confidence: 99%
See 3 more Smart Citations